Two-Year Progress of Pilot Research Activities in Teaching Digital Thinking Project (TDT) - Roland Ambros; Angelika Bernsteiner; Roderick Bloem; Dominik Dolezal; David Garcia; Katrin Göltl; Claudia Haagen-Schützenhöfer; Markus Hadler; Timotheus Hell; Alina Herderich; Petar Jercic; Fares Kayali; et al. (Forum Neue Medien in der Lehre Austria, 2023)
This article presents a progress report from the last two years of the Teaching Digital Thinking (TDT) project. This project aims to implement new concepts, didactic methods, and teaching formats for sustainable digital transformation in Austrian Universities' curricula by introducing new digital competencies. By equipping students and teachers with 21st-century digital competencies, partner universities can contribute to solving global challenges and organizing pilot projects. In line with the overall project aims, this article presents the ongoing digital transformation activities, courses, and research in the project, which have been carried out by the five partner universities since 2020, and briefly discusses the results. This article presents a summary of the research and educational activities carried out within two parts: complementary research and pilot projects.